2019
DOI: 10.1017/ipo.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Do environmental preferences in wealthy nations persist in times of crisis? The European environmental attitudes (2008-2017)

Abstract: How do economic recessions affect European citizens’ attitudes towards environmental policies? In this article we investigate the attitudes of European citizens towards environmental protection considering its importance both at individual and country levels and adopting a longitudinal view. In light of the existing research on the link between pro-environmental attitudes and economic affluence of societies, including Ronald Inglehart’s theory of post-materialism, we hypothesise that levels of economic well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…EEP is highly associated with their cognition, knowledge, awareness and concern for the environment (Gholamzadehmir, Sparks, & Farsides, 2019). According to Benedetta and Vincenzo (2020), it is their environmental attitude which causes different actions by the employee to protect the environment from deterioration. An individual with a positive mindset with respect to environmental importance makes all out efforts to ensure that his actions during job performance do not break the environmental regulations, manage environmental crisis as well as other co‐workers are educated with respect to environmental matters (Paillé & Meija‐Morelos, 2019).…”
Section: Study Background and Hypothesis Developmentmentioning
confidence: 99%
“…EEP is highly associated with their cognition, knowledge, awareness and concern for the environment (Gholamzadehmir, Sparks, & Farsides, 2019). According to Benedetta and Vincenzo (2020), it is their environmental attitude which causes different actions by the employee to protect the environment from deterioration. An individual with a positive mindset with respect to environmental importance makes all out efforts to ensure that his actions during job performance do not break the environmental regulations, manage environmental crisis as well as other co‐workers are educated with respect to environmental matters (Paillé & Meija‐Morelos, 2019).…”
Section: Study Background and Hypothesis Developmentmentioning
confidence: 99%
“…This also followed a period of continuous decline in unemployment since its previous peak in 1993, reaching lows that had not been seen in almost 25 years (Office for National Statistics 2020). One subsequently sees gradual declines tying in with a broader trend of the environment losing salience across Europe between 2002 and 2003 (Benedetta and Vincenzo 2020: 8), falling to 67% in May 2004. Further decline is noted in 2005 with the economic growth and unemployment trade-off question showing prioritization at only 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, inconsistency in questions involving either economy versus environment trade-offs or willingness to make personal financial sacrifices for the environment may be due to economic fluctuations between survey administrations (period 2006-2016), as public opinion on the environment may be affected by short-term economic conditions [15][16][17]. Previous research has found that pro-environmental attitudes [16] and support for environmental protection [17] decrease during unfavorable economic periods [14]. Therefore, we recommend caution when interpreting results associated with low-reliability items.…”
Section: Discussionmentioning
confidence: 99%
“…These two surveys were selected because they are designed to be representative and international in scope and because they ask questions about the environment on a recurring basis and make the results publicly available. Taken together, they cover a wide range of countries around the world, and they have been widely used by researchers seeking to understand global or country-level trends in attitudes over time [14][15][16][17][18][19], along with the determinants and consequences of such trends [20,21]. Cross-national comparisons made possible by such international surveys are critical for identifying dynamics and causal relationships that are not visible when looking only at a single country.…”
Section: Introductionmentioning
confidence: 99%